RANCANG BANGUN APLIKASI E-LEARNING BERBASIS ANDROID DI MIS MUHAMMADIYAH KUBANGKONDANG - Reni Febriani; M. Yusuf Romdoni; Budy Prayoga; Waliadi Gunawan (Journal of Innovation And Future Technology (IFTECH), 2022)
The development of Technology and Communication at thus time has a huge impact, one of which is in the field of education, one form of technological development applied in education is a e-learning. Learning activities at MIS Muhammadiyah Kubangkondang are currently carried out face-to-face where the classroom learning activities when teachers of students cannot be present in class and make students feel freedom in carrying out learning become one of the ideas for the creation of an android-based e-learning application design. The research methodology used is the observation and interview data collection method, and the waterfall system development method and UML data modelling. The programming language used kotlin. With this application, the implementation of learning will continue even though the learning time in the classroom has run out because students can view material through the application outside of study hours, when theacers or students are not present in the classroom can carry out learning because teacher can provide material through the application and students can view material through the application.